ANALISIS PERPRES NO. 113 TAHUN 2021 DITINJAU DARI PUTUSAN MK NO. 91/PUU-XVIII/2020 - Nurfatika; Ferry Edwar (Fakultas Hukum Universitas Trisakti, 2023)
The Law No. 11 of 2020 Concerning Job Creation (Job Creation Law) has been declared to be conditionally unconstitutional by the Constitutional Court Decision No. 91/PUU-XVIII/2020, which means that the articles put up for review have been found to conditionally violate the 1945 Constitution. However, following the reading of the Decision, the Government issued Presidential Regulation No. 113 of 2021 concerning the Structure and Implementation of the Land Bank Agency. This regulation has to do with the Job Creation Law and is in contravention of the Constitutional Court's ruling that the Government must suspend or postpone any policies related to the Job Creation Law. Whether the issue of Presidential Decree No. 113 of 2021 is in accordance with the Constitutional Court Decision No. 91/PUU-XVIII/2020 and what are the legal consequences of the issuance of Presidential Decree No. 113 of 2021. This research uses a normative juridical method. The results of this study indicate that based on the research that has been done, it can be concluded that the issuance of Presidential Decree No. 113 of 2021 violates and contradicts the Constitutional Court Decision No. 91/PUU-XVIII/2020.